(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Excessive breast movement causes breast discomfort, pain and sagging. Previous research has shown that sports bras can support the breasts and reduce breast movement during different activities especially running. However, so far, no published research has studied the design of shoulder straps from a biomechanical modeling perspective, for improving the performance of sports bras. In this study, biomechanical models of shoulder straps with different widths and in different positions on the shoulder have been built, based on the assumptions that the behavior of shoulder straps is similar to that of springs and the front shoulder strap is aligned with the body. The results show that wider shoulder straps are more effective in reducing the breast forces, and the location of the shoulder straps on the shoulder affects their performance in controlling breast movement. This provides a theoretical basis for optimizing the design of shoulder straps to produce more effective sports bras.